Working conditions of immigrant women in household labour market: Murcia City - Prudencio José Riquelme Perea; Encarnación Ruiz Casanova (Atlantic Review of Economics, 2014)
The massive of immigrant women in recent decades, has resulted in social and labour insertion of these effectively enforced through the domestic sector, but in which conditions? The Purpose of this study is to show the functioning of the domestic work market within Murcia City, through information provided by immigrant women (legal or illegal) and Spanish families, who requested services to various non profit organizations.
Keywords: J4; J42; 330; immigrant women; domestic work; supply and demand; labour conditions